Activity of seston polycyclic aromatic hydrocarbons hydroxylase (the tropical zone of the Pacific Ocean) - Коломєйченко, Г. Ю.; Петров, С. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
There have been given the results of the study of seston benzo[a]pyrene hydroxylase activity in water surface of the northeastern part of the tropical zone of the Pacific Ocean. The data obtained have been used for estimation of benzopyrenes metabolism by pelagial ecosystems. The proposed method can serve as an early diagnostic parameter of hydrobionts’ ability to metabolize polycyclic aromatic hydrocarbons.